2022
DOI: 10.30722/ijisme.30.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a Design Thinking Mindset in Educationally Disadvantaged Students Using a Design-based Activity

Abstract: Science, technology, engineering, and mathematics (STEM) education, as an educational policy, provides opportunities for students to learn these disciplines in more integrated ways than traditional methods. This can be pedagogically accomplished via a design-based approach where students engage collaboratively in solving engineering problems using various domains of knowledge and skills. In this pedagogical process, design thinking is vital. However, little is known about whether students develop this kind of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Chusinkunawut et al (2021) observed that students encountered conflict with peers during DBL. Such conflicts can inhibit the development of the collaborative aspect of the DTM (Ladachart, Khamlarsai et al, 2022). Moreover, different students are likely to approach DBL differently (McLean et al, 2020), because of variations in empathic ability (Toussaint & Webb, 2005) and attitudes to collaboration (Bear & Woolley, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chusinkunawut et al (2021) observed that students encountered conflict with peers during DBL. Such conflicts can inhibit the development of the collaborative aspect of the DTM (Ladachart, Khamlarsai et al, 2022). Moreover, different students are likely to approach DBL differently (McLean et al, 2020), because of variations in empathic ability (Toussaint & Webb, 2005) and attitudes to collaboration (Bear & Woolley, 2011).…”
Section: Introductionmentioning
confidence: 99%